Pengaruh Motivasi dan Budaya Organisasi terhadap Kinerja Karyawan Pada PT. Genki Kirana Internusa Cabang Makassar - Andardinata, Ady; Karmila; Basri, Surya Kelana (STIM-LPI Makassar, 2025)
The Influence of Motivation and Organizational Culture on Employee Performance at PT. Genki Kirana Internusa, Makassar Branch.The purpose of this study was to determine the influence of motivation and organizational culture on employee performance at PT. Genki Kirana Internusa, Makassar Branch. The data used in this study were qualitative and quantitative. The data analysis method used was descriptive analysis, followed by correlation coefficient (r) and determination coefficient (R2) tests, t-tests, and F-tests. The results of the study indicate that both partial and simultaneous tests show a positive and significant effect of motivation and organizational culture on employee performance at PT. Genki Kirana Internusa, Makassar Branch.